2014
DOI: 10.1098/rstb.2013.0034
|View full text |Cite
|
Sign up to set email alerts
|

Looking and homing: how displaced ants decide where to go

Abstract: We caught solitary foragers of the Australian Jack Jumper ant, Myrmecia croslandi, and released them in three compass directions at distances of 10 and 15 m from the nest at locations they have never been before. We recorded the head orientation and the movements of ants within a radius of 20 cm from the release point and, in some cases, tracked their subsequent paths with a differential GPS. We find that upon surfacing from their transport vials onto a release platform, most ants move into the home direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 31 publications
6
87
0
Order By: Relevance
“…One testable prediction would be that ants keep their head more horizontally aligned when they perform scanning movements around the yaw axis and/or when they pause along their foraging path (Narendra et al, 2013c), compared with when they are walking (e.g. Wystrach et al, 2014;Zeil et al, 2014). It is also conceivable that there are ways of preprocessing, representing and comparing images that are robust against roll and pitch misalignments, a possibility that remains to be investigated.…”
Section: Implications Of Head Roll Orientation For Visual Navigationmentioning
confidence: 99%
See 1 more Smart Citation
“…One testable prediction would be that ants keep their head more horizontally aligned when they perform scanning movements around the yaw axis and/or when they pause along their foraging path (Narendra et al, 2013c), compared with when they are walking (e.g. Wystrach et al, 2014;Zeil et al, 2014). It is also conceivable that there are ways of preprocessing, representing and comparing images that are robust against roll and pitch misalignments, a possibility that remains to be investigated.…”
Section: Implications Of Head Roll Orientation For Visual Navigationmentioning
confidence: 99%
“…However, it has only recently been considered in the context of the image (snapshot)-matching process (Ardin et al, 2015) that is thought to underlie the use of route and place memories for navigation (reviewed in Collett et al, 2013;Zeil, 2012). Recent studies on the Australian jack jumper ant, M. croslandi , and on the desert ant Melophorus bagoti (Wystrach et al, 2014) have investigated the way in which ants scan the panorama before deciding where to go, and have concluded that the ants do not look at particular features in the environment, but rather appear to perform a more global matching procedure between current and memorised views (Wystrach et al, 2014;Zeil et al, 2014). Confirming the results obtained by Ardin et al (2015) for pitch misalignment, we have shown here that misalignments around the roll axis of more than 10 deg between the memorised reference images and the current views are likely to pose serious problems for retrieving navigational information through such global image comparisons.…”
Section: Implications Of Head Roll Orientation For Visual Navigationmentioning
confidence: 99%
“…Ants in landmark-rich habitats however, including the two species studied here, are guided by the visual panorama, often in preference to path integration information (e.g. [23,25,51,52]). In such cases, spectral information may improve the reliability of navigational cues.…”
Section: (B) Are Australian Ants Special?mentioning
confidence: 99%
“…The 3D flight path and the head yaw orientation were determined frame-by-frame using custom-made software (see [13,16] for details).…”
Section: Recording and Path Reconstruction Of Learning Flightsmentioning
confidence: 99%